2005
DOI: 10.1152/ajplung.00329.2004
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary overexpression of IL-10 augments lung fibrosis and Th2 responses induced by silica particles

Abstract: Barbarin, Virginie, Zhou Xing, Monique Delos, Dominique Lison, and Francois Huaux. Pulmonary overexpression of IL-10 augments lung fibrosis and Th2 responses induced by silica particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 64 publications
4
76
0
2
Order By: Relevance
“…Thus, it remains to be explained why chronic lung inflammation induced by silica is not directed by IL-17-producing T cells as it is during the earlier response. We demonstrated previously that long-term responses to silica in mice are strongly associated with the upregulation of suppressive cytokines, such as IL-10, which control, at least in part, the establishment of chronic inflammation (24,57). Thus, we can speculate that this anti-inflammatory response can control the proinflammatory activities of IL-17A, as demonstrated in several recent reports (13,(58)(59)(60).…”
Section: Discussionsupporting
confidence: 59%
“…Thus, it remains to be explained why chronic lung inflammation induced by silica is not directed by IL-17-producing T cells as it is during the earlier response. We demonstrated previously that long-term responses to silica in mice are strongly associated with the upregulation of suppressive cytokines, such as IL-10, which control, at least in part, the establishment of chronic inflammation (24,57). Thus, we can speculate that this anti-inflammatory response can control the proinflammatory activities of IL-17A, as demonstrated in several recent reports (13,(58)(59)(60).…”
Section: Discussionsupporting
confidence: 59%
“…The results from the study evidenced acute pulmonary inflammation and neutrophil infiltration to the lung tissues in a dose-dependent manner [193]. Similar studies using silica nanoparticles reported induction of anti-inflammatory mediators and reversibility of fibrotic changes [194,195]. A few studies in lung tissues suspected translocation and diffusion of silica nanoparticles away from the lung tissue through systematic circulation and deposition in extra pulmonary organs [196][197][198].…”
Section: Effects On Organ Systemsmentioning
confidence: 55%
“…The toxicity of the titanium oxide nanoparticle was observed when keratinocyte cell line (HaCaT), human dermal fibroblasts and human immortalized sebaceous gland cell lines (SZ95) were used. The cytotoxicity affected cellular functions including differentiation, cell proliferation and mobility which resulted in apoptosis [220].Upregulation of fibrogenic mediators including IL-4, IL-10 and IL-13 was also observed contributing to fibrotic changes [195].…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Although delivery of IL-10 plasmid inhibits bleomycininduced pulmonary fibrosis [27], transgenic mice over expressing IL-10 develop pulmonary inflammation and subepithelial fibrosis with an accumulation of TGF-b1 [28]. In accordance, IL-10 augments the fibrotic responses to inhaled silica particles as seen in IL-10 deficient mice [29] and over expression of IL-10 by adenoviral gene transfer [30]. In vitro, IL-10 also induces TGF-b1 expression in alveolar macrophages [29].…”
Section: Discussionmentioning
confidence: 94%